PENGARUH KONFLIK DAN KEPUASAN KERJA TERHADAP KEINGINAN PINDAH KERJA GURU SD SWASTA DI KECAMATAN JATIASIH - Hendhisca Cipta (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The purpose of this study is to observe the influence of conflict and job satisfaction toward turnover intention of private elementry teachers in District Jatiasih. The research used quantitative approach with a survey method and applied path analysis in testing hyphotesis. It was involving 252 teachers with various gender, background and qualification as the respondents, who were selected in a simple random sampling way. The study revealed several results, which are (1). There is positive direct effect of conflict on turnover intention. (2). There is negative direct effect of job satisfaction on turnover intention, and (3). There is negative direct effect of conflict on jobs satisfaction.